Peran Operasi Militer Dalam Mendukung Upaya Diplomasi dalam Pembebasan Irian Barat - Bobby Adhityo Rizaldi; Jamadin F Sianipar; Syaiful Anwar (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The reconquest of West Irian by the Dutch colonialists was a very tiring and hard struggle. The Dutch had a hidden intention to separate West Irian from Indonesian territory. The Dutch government violated the agreements of the Round Table Conference, the Teak Circle Agreement, and International Law. The Indonesian side carried out military operations on Gurita, Rajawali, Djatayu, and finally the Djayawidjaya military operation to retake West Irian. The purpose of this research is to provide an overview and analysis regarding the attitudes and strategies of the two parties in the West Irian conflict from the aspects of political/diplomatic, military and economic strategy. The writing method uses descriptive analysis method, by analyzing the facts that occurred in the struggle to seize West Irian from Dutch rule, supported by literature studies, literature, national and international scientific journals, theoretical and juridical. The results of the research show that there is a relationship and cooperation between activities in the field of politics/diplomacy and the military sector, because in essence the two fields have the same goal and help each other. To get maximum results, politics/diplomacy needs to be supported by military force, and vice versa military power needs political/diplomatic support to ask for huge costs in winning war goals. The war strategy in the future does not only rely on politics/diplomacy and the role of the military alone, but must involve all other components of national defense and be implemented in its entirety.Keywords: Connection; Cooperation; Politics/Diplomacy; Military.